1992
DOI: 10.1073/pnas.89.20.9489
|View full text |Cite
|
Sign up to set email alerts
|

Origins of genes: "big bang" or continuous creation?

Abstract: Many protein families are common to all cellular organisms, indicating that many genes have ancient origins. Genetic variation is mostly attributed to processes such as mutation, duplication, and rearrangement of ancient modules. Thus it is widely assumed that much of present-day genetic diversity can be traced by common is a significant evolutionary process seems to have been largely ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
244
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(253 citation statements)
references
References 57 publications
8
244
0
Order By: Relevance
“…The hypothesis of overlapping genes origin suggested by Shintani et al (1999) cannot fully explain these phenomena because it is related to 3Ј-end overlaps only and does not consider 5Ј-overlaps at all. Overprinting as the origin of overlapping genes, as suggested by Keese and Gibbs (1992), may provide a better explanation, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of overlapping genes origin suggested by Shintani et al (1999) cannot fully explain these phenomena because it is related to 3Ј-end overlaps only and does not consider 5Ј-overlaps at all. Overprinting as the origin of overlapping genes, as suggested by Keese and Gibbs (1992), may provide a better explanation, …”
Section: Discussionmentioning
confidence: 99%
“…Later, one of the genes lost its original polyadenylation signal, but was able to use a signal that happened to be present on the noncoding strand of the other gene. Keese and Gibbs (1992) suspect that overlapping genes arise as a result of overprinting-a process of generating new genes from preexisting nucleotide sequences. However, both studies were done based on a single pair of eukaryotic overlapping genes.…”
mentioning
confidence: 99%
“…Although the steps required to generate a new gene by gene duplication or gene rearrangement have been characterized, less is known about the birth of new genes de novo. One particularly intriguing mechanism of de novo gene birth is via "overprinting," in which a novel overprinting gene is encoded as an alternate ORF within an ancestral "overprinted" gene (1). Overprinting results in two unrelated functional proteins encoded as overlapping ORFs within the same DNA sequence.…”
mentioning
confidence: 99%
“…Also, availability of whole genome sequences showed that vims genes were often contained totally or partially within another gene, in a different reading frame. This observation led Adrian Gibbs to propose the very novel concept of de novo generation of genes by "overprinting," and methods to analyze which of the two overlapping genes was the novel one (Keese and Gibbs 1992).…”
Section: The Early Periodmentioning
confidence: 99%